Sports massage - Findlay, Susan 1956- (Hands-on guides for therapists, 2010)
This book features 130 full-colour photos that guide you through the essentials of sports massage. This title provides information of foundation massage techniques within sports massage. It also helps you learn how to use advanced working positions in prone, supine, side-lying and sitting orientations to address each muscle group